18F-Fluorodeoxyglucose positron emission tomography/computed tomography as a diagnostic and follow-up tool in Coxiella burnetii endocarditis of prosthetic valve and aortic valved tube: a case report. Issue 5 (17th May 2021) - Ricciardi, Elisa; Moscatelli, Alessandro; Berruti, Marco; Donegani, Maria Isabella; Mikulska, Malgorzata Karolina; Pende, Aldo
Abstract: Background : European Society of Cardiology 2015 guidelines approved 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) as a useful diagnostic imaging technique in prosthetic valve endocarditis (PVE) and recent evidence seems to suggest a role of nuclear imaging in the follow-up of cardiovascular infections, but nowadays there are no sufficient data available. Case summary : A 67-year-old male presented with fever, weight loss, and fatigue. His medical history included ulcerative colitis and a previous Bentall-De Bono surgical procedure in 2014. A previous recent hospitalization to a small community hospital did not reveal a clear aetiology for the fever: transeosophageal echocardiography showed dubious peri-prosthetic tissue alterations, interpreted as post-surgical fibrosis; consequently, the patient was discharged with steroid therapy. At admission in our ward, we repeated transoesophageal echocardiography that confirmed the peri-prosthetic alterations. Moreover, 18 F-FDG PET/CT showed two hypermetabolic areas, one around the prosthetic tube in the aortic bulb and the other in relation with the prosthetic aortic valve. Serological test was positive for Coxiella burnetii infection with consequent beginning of a targeted antimicrobial therapy with oral doxicycline and hydroxychloroquine. Echocardiography, serology, and 18 F-FDG PET/CT follow-up demonstrated a progressive response to treatment and clinical conditions of the patient gradually improved. Discussion : According to guidelines, 18 F-FDG PET/CT can be used in ambiguous PVE to improve diagnostic accuracy of standard techniques. In this case, 18 F-FDG PET/CT combined with echocardiography and serological tests is used not only to better define diagnosis but also for treatment response monitoring during follow-up.